Association between arthritis and hand grip strength indices combined with anthropometry in an older Korean population. - Jeong H Chi; Bum J Lee (PLoS ONE, 2023)
Background Hand grip strength (HGS) is related to arthritis and all-cause mortality. Many studies have examined the association between HGS and arthritis, but these studies did not consider relative HGS indices. The objectives of this study were to examine the association between arthritis and HGS indices in an older Korean population and to compare an absolute HGS index and a relative HGS indices. Methods In a large-scale cross-sectional study, a total of 16,860 subjects older than 50 years from the Korea National Health and Nutrition Survey from 2014 to 2019 were included for statistical analysis. A binary logistic regression model was used to examine the association between arthritis and HGS indices in crude and covariate-adjusted models. Results In the crude analysis, all anthropometric and HGS indices were associated with arthritis except for weight in men. In adjusted models 1 and 2, among the anthropometric indices, waist circumference (WC) and waist-to-height ratio (WHtR) were associated with arthritis in men but not in women. Absolute HGS and all relative HGS indices showed a negative association with arthritis among both men and women, and the magnitude of the association of arthritis with the absolute HGS index and the relative HGS indices was similar. However, the magnitude of the association between all HGS indices and arthritis was higher for men than for women except in the crude analysis. Discussion Absolute and relative HGS indices had negative associations with arthritis, and the magnitude of the association between the absolute HGS index and arthritis and between the relative HGS indices and arthritis was similar in all models. To our knowledge, this is the first report of an association between arthritis and relative HGS indices, which was not observed in previous studies.